Crosstalk between Signaling Pathways in Pemphigus: A Role for Endoplasmic Reticulum Stress in p38 Mitogen-Activated Protein Kinase Activation? - Cipolla, Gabriel A.; Park, Jong Kook; Lavker, Robert M.; Petzl-Erler, Maria Luiza (Frontiers in Immunology, 2017)
Pemphigus consists of a group of chronic blistering skin diseases mediated by autoantibodies (autoAb). The dogma that pemphigus is caused by keratinocyte dissociation (acantholysis) as a distinctive and direct consequence of the presence of autoAb targeting two main proteins of the desmosome – desmoglein (DSG) 1 and/or DSG3 – has been put to the test. Several outside-in signaling events elicited by pemphigus autoAb in keratinocytes have been described, among which stands out p38 mitogen-activated protein kinase (MAPK) engagement and its apoptotic effect on keratinocytes. The role of apoptosis in the disease is, however, debatable, to an extent that it may not be a determinant event for the occurrence of acantholysis. Also, it has been verified that compromised DSG trans-interaction does not lead to keratinocyte dissociation when p38 MAPK is inhibited. These examples of conflicting results have been followed by recent work revealing an important role for endoplasmic reticulum (ER) stress in pemphigus’ pathogenesis. ER stress is known to activate the p38 MAPK pathway, and vice-versa. However, this relationship has not yet been studied in the context of activated signaling pathways in pemphigus. Therefore, by reviewing and hypothetically connecting the role(s) of ER stress and p38 MAPK pathway in pemphigus, we highlight the importance of elucidating the crosstalk between all activated signaling pathways, which may in turn contribute for a better understanding of the role of apoptosis in the disease and a better management of this life-threatening condition.